ZnO/Chitosan Nanoconjugates from Chlorella vulgaris as Nanostimulants Against Viral Nervous Necrosis in Grouper - Yanuhar, Uun; Suryanto, Heru; Evanuarini, Herly; Caesar, Nico Rahman; Machfuda, Defa Rizqi; Wardani, Nezya Pramudya; Ananda, Aisha Surya (Trends in Sciences, 2026)
Grouper farming underpins Indonesia’s coastal livelihoods and supplies both domestic and export markets, yet disease-especially Viral Nervous Necrosis (VNN) in juveniles-remains a major constraint. Conventional tools (antibiotics, standard vaccines) have delivered limited protection, motivating alternative approaches. Leveraging nanotechnology, we evaluated a ZnO-chitosan nanoconjugate carrying a recombinant Chlorella vulgaris antigen for antiviral protection in cantang grouper (E. fuscoguttatus×E. lanceolatus). In a 56-day randomized block trial, 160 fish were allocated to 5 treatments (T1 - T5) and two controls. Endpoints included growth (length, weight, survival rate, SR; relative percent survival, RPS), hematology (erythrocytes, leukocytes, hematocrit, hemoglobin), gill histopathology, and flow cytometry of CD4⁺/CD8⁺ T-cell markers. The 33 µL regimen (T3) was consistently superior: length rose from 9.94 → 12.73 cm and weight from 13.57 → 18.00 g, with SR = 95% and RPS = 92%. Hematological profiles improved across all indices; gill lesions were minimal (mild edema, hyperplasia, lamellar fusion); and immunophenotyping showed moderated CD4⁺ activation alongside a marked increase in CD8⁺ expression, indicating effective cellular immunity. While T1 and T4 performed well and T2/T5 yielded moderate responses, T3 delivered the most balanced protection and significantly lowered viral load. These results highlight the promise of recombinant Chlorella antigens formulated in ZnO-chitosan nanoconjugates to strengthen grouper health and bolster aquaculture sustainability. HIGHLIGHTS Recombinant Chlorella vulgaris combined with ZnO/Chitosan nanoconjugates significantly enhanced grouper fish growth, immune response, and survival against Viral Nervous Necrosis (VNN). Optimal nanovaccine dose (33 µL) resulted in the highest Survival Rate (95%) and Relative Percent Survival (92%) compared to control groups. Nanostimulants improved hematological parameters (RBC, WBC, Hb, Hct), indicating better overall fish health and immune function. Histopathology showed reduced tissue damage in the gills (mild edema, hyperplasia, and lamella fusion), suggesting the nanovaccine mitigates viral-induced damage. Flow cytometry analysis revealed controlled T-cell activation, indicating a well-balanced immune response and avoiding excessive immune stimulation. GRAPHICAL ABSTRACT